Plantas de cobertura influenciam a efetividade de agentes de controle biológico e plantas de cobertura no manejo de Pratylenchus brachyurus e Helicotylenchus dihystera na cultura da soja. - Karoline Günther (2023)
One of the main strategies for nematode management is the use of cover crops. However, as well as the influence on nematodes, the cover crops can also change the dynamics of biological control agents. The purpose of this work was to evaluate the interaction between biological control agents and different cover crops in the population control of root lesion nematode (Pratylenchus brachyurus) and spiral nematode (Helicotylenchus dihystera) in soybean. The experiment was carried out in the 2021/22 harvest using an experimental delineation, in randomized blocks in a factorial scheme, with levels composed of cover crops (Crotalaria spectabilis, Brachiaria ruziziensis, corn, and fallow) and biological agents: Control; Bacillus subtilis + B. licheniformis; B. methylotrophicus; Purpureocillium lilacinum + Trichoderma harzianum; Pochonia chlamydosporia and Abamectin, a total of 6 treatments. At 15 days after planting, agronomic analysis of the initial stand, root length, weight, and plant height were performed for both targets. At the time of planting (0), 30, 60, and 90 days, population analysis of Pratylenchus brachyurus and Helicotylenchus dihystera present in the soil and roots was carried out. After the soybean harvest, the following cover crops were sown in addition to the fallow area: Crotalaria spectabilis, Brachiaria ruziziensis, and Zea mays. For the cover crops, nematode analysis was carried out 90 days after planting. For the stand, the use of Bacillus spp. and P. lilacinum + T. harzianum promoted better plant growth, while for the variables height, length, and root weight, the coverings presented better performance, with emphasis on crotalaria and brachiaria. For root lesion nematode and Helicotylenchus dihystera, treatments composed of Bacillus spp. revealed the highest percentage of reduction 90 days after planting. The use of biological products is efficient in terms of agronomic characteristics and reduction of nematode population levels. For productivity, the highest averages were obtained using products based on Bacillus spp. and Crotalaria spectabilis. There was no interaction between biological control agents and cover crops. The use of biological products is efficient in terms of agronomic characteristics and reduction of nematode population levels. The cover crops that did not favour nematode multiplication were crotalaria, brachiaria, and fallow for P. brachyurus and brachiaria for H. dihystera.